First enantioselective total synthesis and configurational assignments of suberosenone and suberosanone as potential antitumor agents. Issue 16 (28th January 2015) - Kousara, Mohammad; Ferry, Angélique; Le Bideau, Franck; Serré, Kathalyn L.; Chataigner, Isabelle; Morvan, Estelle; Dubois, Joëlle; Chéron, Monique; Dumas, Françoise
Abstract : The first enantioselective syntheses of (1 R )-suberosenone and (1 R )-suberosanone are achieved, leading to revision of the AC of a natural (1 S )-suberosanone. Abstract : The first enantioselective total syntheses of two marine sesquiterpenes (1 R )-suberosenone and (1 R )-suberosanone are achieved leading to revision of the AC of natural (1 S )-suberosanone. Key elements of the synthesis include hyperbaric asymmetric Michael addition and highly efficient silver trifluoroacetate mediated α-alkylation for the formation of ring A.